2023
DOI: 10.3389/fmicb.2023.1094311
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of geothermal microbial communities in Aotearoa-New Zealand

Abstract: Microbial biogeography studies, in particular for geothermal-associated habitats, have focused on spatial patterns and/or individual sites, which have limited ability to describe the dynamics of ecosystem behaviour. Here, we report the first comprehensive temporal study of bacterial and archaeal communities from an extensive range of geothermal features in Aotearoa-New Zealand. One hundred and fifteen water column samples from 31 geothermal ecosystems were taken over a 34-month period to ascertain microbial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Despite its high abundance, this MAG (Erebus-TR_bin. 23 given that Archaea are generally much more dispersal limited than Bacteria (56). Our hope is that further microbial explorations at these unique sites, with broader sampling at more areas and further metagenomic, transcriptomic, and culturing work, will help uncover the wealth of novel microorganisms present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its high abundance, this MAG (Erebus-TR_bin. 23 given that Archaea are generally much more dispersal limited than Bacteria (56). Our hope is that further microbial explorations at these unique sites, with broader sampling at more areas and further metagenomic, transcriptomic, and culturing work, will help uncover the wealth of novel microorganisms present.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Antarctic geothermal regions serve as enrichment zones for thermophiles, given the vast amount of ice and snow separating regions and the extremely cold air conditions in Antarctica, resulting in little regional influence of non-thermophiles on the microbial communities present. Interestingly, past studies of thermophiles, mainly in hot spring environments, have found high niche specialization for temperature or pH, with environmental selection being the primary factor influencing community assembly and low dispersal rates between sites (20)(21)(22)(23)(24). It is unknown whether the strong winds in Antarctica are capable of overcoming the generally low dispersal rates for thermophiles at Antarctic geothermal regions.…”
Section: Introductionmentioning
confidence: 99%
“…There is therefore a critical need to develop new approaches, techniques, and infrastructure to assess responses of subsurface biospheres to geologic processes, particularly in volcanically and seismically active regions. As of now, they are mainly investigated through their surface manifestations (hot springs), which indicate that subsurface microbial communities are acutely responsive and sensitive to spatial changes in the physicochemical composition of aquifers sourcing the springs (Colman et al, 2021;Fullerton et al, 2021;Power et al, 2023). Collectively, these studies are strong indicators that subsurface litho-autotrophic microbial ecosystems (SliMEs) in hydrothermal systems would similarly be responsive to input of geogenic electron donors or acceptors, regardless of the process involved (e.g.…”
Section: Topic 3: Deep Biosphere Diversity Function and Geobiological...mentioning
confidence: 99%
“…For example, Erebus-TR_bin. 23.permissive_ nal (class Nitrososphaeria), present at all four sites, has a limited metabolic repertoire (genes for aerobic CO oxidation, chlorite reduction, nitrite reduction, and sulfur oxidation), with mostly aerobic pathways (Fig. 6C).…”
Section: Functional Imprint Of Habitat Specializationmentioning
confidence: 99%
“…Finally, Antarctic geothermal regions serve as enrichment zones for thermophiles, given the vast amount of ice and snow separating regions and the extremely cold air conditions in Antarctica, resulting in little regional in uence of non-thermophiles on the microbial communities present. Interestingly, past studies of thermophiles, mainly in hot spring environments, have found high niche specialization for temperature or pH, with environmental selection being the primary factor in uencing community assembly and low dispersal rates between sites (20)(21)(22)(23)(24). It is unknown whether the strong winds in Antarctica are capable of overcoming the generally low dispersal rates for thermophiles at Antarctic geothermal regions.…”
Section: Introductionmentioning
confidence: 99%